2007
DOI: 10.20452/pamw.85
|View full text |Cite
|
Sign up to set email alerts
|

Influence of birthweight and current body mass on cardiovascular risk factors in young adults

Abstract: Introduction. Results of other studies indicate at increased predisposition of metabolic diseases in the adulthood in subjects born with low birthweight. Objectives. To estimate the prevalence of cardiovascular risk factors in adults in relation to birthweight and current body mass. Patients and methods. The study was performed in 498 subjects aged 24-29 years, born in Warsaw in 1974-1977, whose mothers during pregnancy participated in a prospective study of risk factors of low birthweight. Basic anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Low birthweight is known to be related with an adverse glucose and insulin profile in adult life [ 45 ], although, the relationship is less clear regarding HbA 1c . In line with our findings, most of studies did not find any association between birthweight and HbA 1c in children [ 46 ], adolescents [ 36 ] and adults [ 47 ]; while a recent study carried out in English children found a 0.04% increase in HbA 1c for every 100 g of lower birthweight [ 48 ]. The mentioned association appeared after adjustment for current height and became stronger with further adjustment for body fatness, indicating that the association depends on childhood size more than birthweight per se.…”
Section: Discussionsupporting
confidence: 91%
“…Low birthweight is known to be related with an adverse glucose and insulin profile in adult life [ 45 ], although, the relationship is less clear regarding HbA 1c . In line with our findings, most of studies did not find any association between birthweight and HbA 1c in children [ 46 ], adolescents [ 36 ] and adults [ 47 ]; while a recent study carried out in English children found a 0.04% increase in HbA 1c for every 100 g of lower birthweight [ 48 ]. The mentioned association appeared after adjustment for current height and became stronger with further adjustment for body fatness, indicating that the association depends on childhood size more than birthweight per se.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are partly supportive of those reported by Aceti et al, where there was no significant difference in BP in the unadjusted analysis; however, when adjusted for covariates such as age and gender, systolic BP was higher while there was no difference in diastolic BP in the exposed children. 15 This elevation in BP may be mediated through upregulation of endothelial markers such as E-selectin and vascular adhesion molecule 1, 71 which are known to cause vascular dysfunction, 72 thus leading to elevated BP. In the unadjusted analysis for exposure to preeclampsia, we reported a small (∼2 mm Hg) but significant increase in systolic and diastolic BP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in adult male subjects born at term reported an inverse relationship between bithweight and insulin resistance [135]. Fetal undernutrition may also program metabolic disorders because it may reduce glucose uptake and increase gluconeogenesis in the liver, increase lipid peroxidation in the muscles and reduce insulin inhibition of lipolysis in adipose tissue [136]. Moreover, the enhanced risk of metabolic syndrome development in subjects born with IUGR has been associated with an increased cortisol release [137].…”
Section: Growth Related Hormones and Metabolic Alterationsmentioning
confidence: 98%